Influence of Climate on the Homeopathic Prescription - van Woensel, Erik (Homœopathic Links, 2018)
The different types of climate our patients are sensitive to and their physical generals are frequently overlooked in case-taking; yet, this particular source of information provides us with the key to unlock the door to the correct homeopathic remedy.
Keywords: Climate influences; Physical generals; Kali carbonicum; Rhus toxicodendron; Medorrhinum; Sulphur